Impact of Golden Nutrition Booklet (GNB) in knowledge and attitude changes of balanced nutrition implementation in women childbearing age - Nurul Jannatul Wahidah; Revi Gama Hatta Novika; Siti Nurhidayati; Atriany Nilam Sari; Rufidah Maulina; Luluk Fajria Maulida; Riswi Alida Fatmawati; Tsabita Hanan Mufidah; Anjani Nur Azizah; Arina Dinal Haquw; Nurul Ismatun Khasanah; Sari Oktantri Setiani; et al. (Journal of Health Technology Assessment in Midwifery, 2023)
Factors that lead stunting incidents are poor nutrition and inadequate psychosocial stimulation. Most parent especially in childbearing age may have lack of education about balanced nutrition that impact their feeding implementation to their children. This study investigated the impact of Golden Nutrition Booklet (GNB) in knowledge and attitudes changes of balanced nutrition implementation in women of childbearing age. Altogether 38 women in childbearing age were included in this quasi-experiment study, one group pre-test and post-test design. Â Before the intervention, respondents were given pre-test questionnaire to assess their knowledge and attitude about balance nutrition, then given the GNB to be read during the next 7 days. In the last day, the assessment was repeated after the health education by GNB given. The study showed that health education interventions regarding GNB directly influence the increasing knowledge and attitude outcomes of women of childbearing age p <0.05. However, we can conclude that the GNB can be used as health education media for woman to implementing balanced nutrition, that could enhance child nutrition outcomes.